Is the tax policy counter-cyclical in the Czech Republic? - Klusáčková, Hana (2011)
Goal of this thesis is to evaluate the fiscal and tax policies in terms of pro-cyclicality and counter-cyclicality. The first three chapters deal with the theoretical part. In this part are issues such as fiscal and tax policy, national budget and various types of balances, the economic cycle and it's phases, the concept of counter-cyclical policy of economic theories and also the Pact of Stability and Growth and content of Convergence program of the Czech Republic. The practical part includes an analysis of these policies on the basis of the Czech Republic. The practical part includes an analysis of these policies on the basis of specific figures and evaluation of the results obtained.